2021
DOI: 10.1007/s13762-020-03103-2
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption potentials of iron-based metal–organic framework for methyl orange removal: batch and fixed-bed column studies

Abstract: In the present work, continuous ixed-bed column and batch studies were undertaken to investigate the eiciency of ironbased metal-organic framework (Fe-BTC) for the removal of methyl orange as a model contaminant from aqueous solutions. The batch experiments were carried out by varying operational parameters such as adsorbent dosage, pH, temperature, and initial contaminant concentration. The results showed that Fe-BTC had a high removal eiciency under a wide pH range. The equilibrium data were best itted by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The breakthrough time decreased with increasing concentration, and at higher concentration a sharp rise, and at lower concentration a flattened rise in the BTC was observed. The saturation on active sites on the adsorbent saturated quickly at 40 mg/L, thereby exhausting column earlier than other concentrations (Afroze et al 2016;Karami et al 2021).…”
Section: Study With the Varying Concentrationmentioning
confidence: 99%
“…The breakthrough time decreased with increasing concentration, and at higher concentration a sharp rise, and at lower concentration a flattened rise in the BTC was observed. The saturation on active sites on the adsorbent saturated quickly at 40 mg/L, thereby exhausting column earlier than other concentrations (Afroze et al 2016;Karami et al 2021).…”
Section: Study With the Varying Concentrationmentioning
confidence: 99%
“…This study suggests that while increasing bed depth can enhance adsorption capacity, there exists an optimal bed height beyond which further increases do not necessarily lead to higher qeq. In a study by Karami et al [20], the adsorption potentials of an iron-based metal-organic framework (Fe-BTC) for methyl orange removal were examined through both batch and fixed-bed column studies. The research showed that at bed depths of 0.75 and 1.5 cm, the breakthrough times were 20.0 and 46.2 h, respectively, with maximum adsorption capacities of 20.2 and 21.6 mg/g.…”
Section: Effect Of Bed Depth On Breakthrough Curvementioning
confidence: 99%
“…One major component of industrial wastewater effluents is the discharge of a substantial amount of synthetic dyes due to their wide-ranging applications, including in textiles, printing, plastic, and food processing [13,14]. To prevent any potential hazards caused by these dyes to the surrounding environment of aquatic life and humans [15], industrial wastewater effluents are usually treated by several physical and/or chemical treatment processes to remove these synthetic dyes [16]. These treatments include flocculation combined with flotation, electroflocculation, membrane filtration, electrokinetic coagulation, electrochemical destruction, and ion exchange [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, activated carbon (AC) is used as an adsorbent for quickly capturing dyes from wastewater and lowering their concentration in effluents. However, AC as an adsorbent generally shows very little selectivity over molecules of different sizes and has a high regeneration cost when exhausted [16]. Therefore, the development of efficient and cost-effective adsorbents is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation